Comparative analysis of approaches to measure the cost of casualties and fatalities in road safety: guidelines for Peru - Diaz Valer, Nuria Jasira (2020)
Descargue el texto completo en el repositorio institucional de la Universiteit Hasselt: http://hdl.handle.net/1942/32387